Expert consensus on evidence-based recommendations for the diagnosis, treatment, and follow-up of X-linked hypophosphatemic rickets (XLH) (2024)
Introduction: X-linked hypophosphatemic rickets is a hereditary condition causing disruptions in bone mineral homeostasis. The morbidity associated with this condition has exhibited variability in previous decades, possibly stemming from variations in case definitions and diagnostic confirmation procedures. Objective: Our aim was to generate evidence-informed recommendations for the diagnosis, treatment, and follow-up of patients with suspected or diagnosed XLH. Methodology: Integration of a literature review with a modified Delphi method, guided by expert consensus. Results: Following the screening and selection of 1041 documents, 41 were chosen to address the queries posed by the developer group. Experts, consulted through a modified Delphi consensus, endorsed 97 recommendations on the diagnosis, treatment, and follow-up of patients with suspected or diagnosed XLH. Notably, the quality of the evidence was deemed to be low. Conclusions: The recommendations proposed here will allow early and timely diagnosis of Xlinked hypophosphatemic rickets, while optimizing resources for its treatment and follow-up. In addition, it will help clarify the burden of the disease and improve health outcomes for this population.